2023
DOI: 10.3390/ijms24044234
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA BNIP3 Inhibited the Proliferation of Bovine Intramuscular Preadipocytes via Cell Cycle

Abstract: The intramuscular fat (or marbling fat) content is an essential economic trait of beef cattle and improves the flavor and palatability of meat. Several studies have highlighted the correlation between long non-coding RNAs (lncRNAs) and intramuscular fat development; however, the precise molecular mechanism remains unknown. Previously, through a high-throughput sequencing analysis, we found a lncRNA and named it a long non-coding RNA BNIP3 (lncBNIP3). The 5′ RACE and 3′ RACE explored 1945 bp total length of lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…The CDC6 gene is a key gene in the regulation of the human cell cycle, and it plays an important role in DNA replication and cell division ( Hofmann et al., 2011 ; Shi et al., 2021 ; Zhang et al., 2023 ). Recent studies have shown that the CDC6 gene plays an important role in a variety of tumors, including gliomas ( Wang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDC6 gene is a key gene in the regulation of the human cell cycle, and it plays an important role in DNA replication and cell division ( Hofmann et al., 2011 ; Shi et al., 2021 ; Zhang et al., 2023 ). Recent studies have shown that the CDC6 gene plays an important role in a variety of tumors, including gliomas ( Wang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the genes with the largest changes in logFC values were not chosen is that we preferentially compared differential signaling pathways analyzed possible protein regulatory networks and changes in logFC values, and combined with previous studies, we found significant changes in CDC6-related signaling pathways. The CDC6 gene is a key gene in the regulation of the human cell cycle, and it plays an important role in DNA replication and cell division (Hofmann et al, 2011;Shi et al, 2021;Zhang et al, 2023). Recent studies have shown that the CDC6 gene plays an important role in a variety of tumors, including gliomas (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…É importante destacar que lncRNA é classe do material genético transcrito de tamanho maior que 200 nucleotídeos [Xu et al 2022] e que não codifica proteínas [Statello et al 2021]. Diferentemente do que era pensado até então, um lncRNA não pode ser categorizado como parte do DNA não fundamental aos seres vivos [Zhang et al 2023], uma vez que é essencialmente complexos e desempenha diversas func ¸ões nos diferentes organismos [Kopp and Mendell 2018].…”
Section: Informac ¸õEs Geraisunclassified